2022
DOI: 10.1139/cjb-2021-0138
|View full text |Cite
|
Sign up to set email alerts
|

Leaf ontogenesis of Trembleya phlogiformis DC. (Microlicieae, Melastomataceae): functional aspects and indumentum characterization

Abstract: Leaf ontogenesis is determinant for the establishment and regulation of its structural and functional properties, in addition to being an excellent tool for assignment to different groups of angiosperms. Even though the importance of leaf morphology and anatomy for taxonomic use is well known, few studies have addressed the processes of leaf ontogeny in Melastomataceae. Herein, we sought to define the ontogenetic steps of leaf of Trembleya phlogiformis, highlighting the indumentum, to understand the main funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Since amphistomy and hypostomy have been reported in Lavoisiereae (see Silva et al 2018;Carmo et al 2019Carmo et al , 2020Romero et al 2021a), which has species distributed in different microhabitats (Fritsch et al 2004), the tribe can be an excellent model to test the relationship between anatomical leaf traits and vegetation/habitat type. The short-stalked glandular trichomes found in M. arenaria, M. dentisepala, and M. membranacea, referred to as spherical glands here, are typically observed in species of the tribe (Silva et al 2018;Carmo et al 2019Carmo et al , 2020Romero et al 2021aRomero et al , 2021bLima et al 2022). It is important to mention that these spherical glands have been named with different terms such as "glandular punctations" (Wurdack 1981;Koschnitzke and Martins 2007;Pacifico and Almeda 2018), "unfurrowed sessile glands" (Wurdack 1986) glands" (Romero et al 2017), and "gland-tipped trichomes" (Pacifico et al 2020a).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Since amphistomy and hypostomy have been reported in Lavoisiereae (see Silva et al 2018;Carmo et al 2019Carmo et al , 2020Romero et al 2021a), which has species distributed in different microhabitats (Fritsch et al 2004), the tribe can be an excellent model to test the relationship between anatomical leaf traits and vegetation/habitat type. The short-stalked glandular trichomes found in M. arenaria, M. dentisepala, and M. membranacea, referred to as spherical glands here, are typically observed in species of the tribe (Silva et al 2018;Carmo et al 2019Carmo et al , 2020Romero et al 2021aRomero et al , 2021bLima et al 2022). It is important to mention that these spherical glands have been named with different terms such as "glandular punctations" (Wurdack 1981;Koschnitzke and Martins 2007;Pacifico and Almeda 2018), "unfurrowed sessile glands" (Wurdack 1986) glands" (Romero et al 2017), and "gland-tipped trichomes" (Pacifico et al 2020a).…”
Section: Methodsmentioning
confidence: 99%
“…Anatomical studies have revealed that these glands correspond to short-stalked glandular trichomes and should not be described as sessile (Cassiano et al 2010;Romero and Castro 2014;Romero et al 2015Romero et al , 2017Romero et al , 20192021a;Silva et al 2018;Carmo et al 2019). Additionally, long-stalked glandular trichomes, similar to those found in M. membranacea are described in some taxa (Silva et al 2018;Carmo et al 2019;Lima et al 2022). The leaf indumentum in Lavoisiereae exhibits considerable variation, even within the same species, encompassing different types of glandular and non-glandular trichomes and emergences (see Silva et al 2018;Carmo et al 2019;Lima et al 2022).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations